Fabrication of sub-nanometer pores on graphene membrane for ion selective transport. Issue 11 (6th March 2018) - Qi, Han; Li, Zhongwu; Tao, Yi; Zhao, Weiwei; Lin, Kabin; Ni, Zhenhua; Jin, Chuanhong; Zhang, Yan; Bi, Kedong; Chen, Yunfei
Abstract : Oxygen plasma-treated graphene membranes can selectively transport protons, Na + and Cl − ions, whereas argon plasma-treated graphene membranes cannot. Abstract : The ability to sieve ions through nanopores with high throughput has significant importance in seawater desalination and other separation applications. In this study, a plasma etching process has been demonstrated to be an efficient way to produce high-density nanopores on graphene membranes with tunable size in the sub-nanometer range. Besides the pore size, the nanopore density is also controllable through adjusting the exposure time of the sample to argon or oxygen plasma. The plasma-treated graphene membranes can selectively transport protons, Na + and Cl − ions. Density function theory calculations uncover that the sp 3 and vacancy-type defects construct different energy barriers for different ions, which allow the defected graphene membrane to selectively transport ions. Our study indicates that oxygen plasma etching can be used as a very convenient and efficient method for fabricating a monolayer filtration graphene membrane with tunable sub-nanometer pores.